Second language learning anxiety among Malay learners of English / Razlina Muhammad Sabri - Muhammad Sabri, Razlina (2010)
This is a study of second language speaking anxiety among Malay ESL learners at an institution of higher learning. The objectives of this study are to determine whether learners experience test anxiety during public speaking, to discover if there is a difference in the anxiety level of high and low proficiency learners, to ascertain whether there are any differences between the high and low anxiety learners in their speaking test assessment, and to identify the factors leading to speaking language anxiety. This study has taken both quantitative and qualitative approaches. The data is mainly obtained from questionnaires and interviews with selected participants, as well as the scores of the speaking assessment. The participants chosen for this study consist of 39 learners from low and high proficiency groups. The theoretical framework rests on Phillips’ (1992) notion that speaking does evoke anxiety among language learners, not only in language classes but more so in test situations. The three main variables being investigated in this study are second language learners, speaking skill and test anxiety. The main findings suggest that both low and high proficiency learners experience anxiety during speaking tasks, specifically in test situations. Besides, as found in other studies by Kondo (2005) and Woodrow (2007), low anxiety learners also performed better than high anxiety learners in this study. However, the findings of this study also showed differences emerged between the high and low proficiency learners where the reasons for experiencing anxiety were concerned. Therefore, it is apparent that low and high proficiency learners experience anxiety, but the reasons for it differ from one group to another.